2013
DOI: 10.1155/2013/848237
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bis-2,3-dihydroquinazolin-4(1H)-ones and 2,3-Dihydroquinazolin-4(1H)-ones Derivatives with the Aid of Silica-Supported Preyssler Nanoparticles

Abstract: One-pot three-component condensation of isatoic anhydride with primary amines or ammonium carbonate and aromatic aldehydes in refluxing ethanol in the presence of catalytic amounts of silica-supported preyssler nanoparticles (SPNP) afforded the corresponding 2,3-dihydroquinazolin-4(1H)-ones in high yields, and bis-dihydroquinazolinones were synthesized for the first time by a novel pseudo-five-component condensation of isatoic anhydride, a primary amine, and a dialdehyde in water. The catalyst is reusable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…94 The integration of mesoporous silica with magnetic NPs is certainly of great interest for practical applications. As shown in Table 3, different silica-supported NPs were used as catalysts for the one-pot three-component reaction, leading to 45-97% yield in 1-8 h. [95][96][97][98][99] The use of solid acids, as non-toxic, low-cost and reusable catalysts, has also emerged in the synthesis of DHQs (Table 3). Among them, several acids bearing sulfonic moiety supported on silica catalyzed the multi-component synthesis under different conditions, providing DHQs with >70% yield in 0.5-7 h. [100][101][102][103][104] MCM-41 is another type of ordered mesoporous silica material.…”
Section: Heterogeneous and Reusable Catalystsmentioning
confidence: 99%
“…94 The integration of mesoporous silica with magnetic NPs is certainly of great interest for practical applications. As shown in Table 3, different silica-supported NPs were used as catalysts for the one-pot three-component reaction, leading to 45-97% yield in 1-8 h. [95][96][97][98][99] The use of solid acids, as non-toxic, low-cost and reusable catalysts, has also emerged in the synthesis of DHQs (Table 3). Among them, several acids bearing sulfonic moiety supported on silica catalyzed the multi-component synthesis under different conditions, providing DHQs with >70% yield in 0.5-7 h. [100][101][102][103][104] MCM-41 is another type of ordered mesoporous silica material.…”
Section: Heterogeneous and Reusable Catalystsmentioning
confidence: 99%
“…We believe that the present methodology addresses the current drive toward green chemistry due to high yields, atomic economy, and reusability of the catalyst. By the reaction of a range of amines and dialdehydes, novel libraries of bisdihydroquinazolinones could be obtained, which would make this method a suitable candidate for combinatorial and parallel synthesis in drug discovery [107] (Schemes 3.48, 3.49, and 3.50). -dione derivatives via one-pot reaction of 3-methyl-1-phenyl-1H-pyrazol-5-amine, arylaldehydes, and 2-hydroxynaphthalene-1,4-dione in water as green solvent and using cerium oxide nanoparticles (CONPs) as a heterogeneous catalyst.…”
Section: Roh + Omentioning
confidence: 99%
“…Recently, 2,3‐ Dihydroquinazolin‐4(1H)‐ones stimulated extensive interest for their anticonvulsant, antiparkinsonian, antihypertensive, antibacterial, anticancer, diuretic, as well as monoamine oxidase inhibition and plant growth regulation . There are numerous classical synthetic methods for synthesizing such important compounds using various acids as catalyst like MCM‐41‐Ni coordinated mesoporous, GO nanosheets, Fe 3 O 4 ‐GO and also preliminary endeavors; TiCl 4 ‐Zn, Sc(OTf) 3 , NH 4 Cl, I 2 /KI and solvent as an oxidant, VO(acac) 2 ‐oxidizer, heteropolyacids and T3P™ . In deeper surveys, it is revealed that enantioselective additives also have had an important place for an investigation .…”
Section: Introductionmentioning
confidence: 99%